2019
DOI: 10.1016/j.jaci.2018.08.053
|View full text |Cite
|
Sign up to set email alerts
|

Mast cell corticotropin-releasing factor subtype 2 suppresses mast cell degranulation and limits the severity of anaphylaxis and stress-induced intestinal permeability

Abstract: Mast cell corticotropin-releasing factor subtype 2 suppresses mast cell degranulation and limits the severity of anaphylaxis and stress-induced intestinal permeability. Permalink https://escholarship.org/uc/item/8t3660m4 Journal Abstract 33 34 Background: Psychological stress and heightened MC activation are linked with important 35 immunological disorders including allergy, anaphylaxis, asthma, and functional bowel 36diseases, but the mechanisms remain poorly defined. We have previously demonstrated that 37 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 44 publications
2
54
0
Order By: Relevance
“…We have recently shown presence of CRF receptors on mast cells [18], enteric neurons, pancreatic acinar cells [16], and fibroblasts [29]. We have also shown increased mast cell infiltration in the gut in a rat model of functional dyspepsia, a gut-brain disorder [19].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have recently shown presence of CRF receptors on mast cells [18], enteric neurons, pancreatic acinar cells [16], and fibroblasts [29]. We have also shown increased mast cell infiltration in the gut in a rat model of functional dyspepsia, a gut-brain disorder [19].…”
Section: Resultsmentioning
confidence: 99%
“…CRF 1 activation initiates HPA responses and anxiety-like behavior, whereas CRF 2 activation brings systems back to homeostasis, and mediates anxiolytic behavior [11,12]. We have shown that CRF 2 plays a vital role in mediating metabolic [13] and immune responses [14,15,16,17,18,19]. CRF 2 receptor dysfunction is known to exacerbate edema, necrosis, and delayed healing [14,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, they contain vast CRF stores (Theoharides and Konstantinidou, 2007). A recent study showed that CRF2 represents a negative modulator of MC activation, suggesting a crucial homeostatic role of MC in the CRF system and in the disorders associated with his (D’Costa et al, 2019).…”
Section: Overview On Mast Cellsmentioning
confidence: 99%
“…14,25 Blockade of peripheral CRF receptors or treatment with mast cell stabilizers will block these effects on the intestinal barrier, confirming the role of mast cells in altering barrier permeability following physical and psychological stress. 14,19,37 Mast cell activation induced by stress could play a key role in the effects seen in the present study, and it is likely that it takes longer than a brief period of transport for these responses to take place. As these barrier effects follow the upregulation of mucosal CRF localized to mast cells, which may also need time to marginate into the tissue from circulation, mast cell responses to stress may partly explain why intestinal barrier repair responses are different in the period immediately after a brief transport stress as compared to more prolonged environmental change over several days.…”
Section: Discussionmentioning
confidence: 82%